3′-Terminated Overhangs Regulate DNA Double-Strand Break Processing in Escherichia coli. Issue 9 (1st September 2017) - Đermić, Edyta; Zahradka, Davor; Vujaklija, Dušica; Ivanković, Siniša; Đermić, Damir
Abstract: Double-strand breaks (DSBs) are lethal DNA lesions, which are repaired by homologous recombination in Escherichia coli . To study DSB processing in vivo, we induced DSBs into the E. coli chromosome by γ-irradiation and measured chromosomal degradation. We show that the DNA degradation is regulated by RecA protein concentration and its rate of association with single-stranded DNA (ssDNA). RecA decreased DNA degradation in wild-type, recB, and recD strains, indicating that it is a general phenomenon in E. coli . On the other hand, DNA degradation was greatly reduced and unaffected by RecA in the recB1080 mutant (which produces long overhangs) and in a strain devoid of four exonucleases that degrade a 3′ tail (ssExos). 3′–5′ ssExos deficiency is epistatic to RecA deficiency concerning DNA degradation, suggesting that bound RecA is shielding the 3′ tail from degradation by 3′–5′ ssExos. Since 3′ tail preservation is common to all these situations, we infer that RecA polymerization constitutes a subset of mechanisms for preserving the integrity of 3′ tails emanating from DSBs, along with 3′ tail's massive length, or prevention of their degradation by inactivation of 3′–5′ ssExos. Thus, we conclude that 3′ overhangs are crucial in controlling the extent of DSB processing in E. coli . This study suggests a regulatory mechanism for DSB processing in E. coli, wherein 3′ tails impose a negative feedback loop on DSB processing reactions, specifically on helicase reloading onto dsDNA ends.